Sinister Looking Lump: A Rare Case of Palmar Rhinosporidiosis in Disguise of Soft Tissue Sarcoma - Soumyadip Das; Mouli Mishra; Sangita Majumder; Chhanda Das; Gopinath Barui (International Journal of Human and Health Sciences (IJHHS), 2026)
Rhinosporodiosis may have varied presentations including tumor like masses at various extra nasal sites. It is challenging at times to distinguish them with malignant soft tissue neoplasms on basis of clinical and radiological findings alone. Cytology and histopathology may prove to be very useful to ascertain the exact nature of such ambiguous lesions. Strong clinical acumen, coupled with knowledge of extra nasal sites and diverse presenting features may help us in making a proper diagnosis. A rare occurrence of palmar rhinosporidiosis has been documented in this case report. International Journal of Human and Health Sciences Vol. 10 No. 04 Oct’26 Page: 300-303